Demographic, Clinical, and Antiretroviral Regiment Treatment Characteristics of HIV/AIDS Patients at the Regional General Hospital of Central Papua - Mar’ah, Siti Sitatul; Ichsan, Burhannudin; Cholisoh, Zakky (Pharmacon: Jurnal Farmasi Indonesia, 2023)
The incidence of HIV infections in Papua is currently on the rise, primarily due to restricted access to antiretroviral treatment and insufficient support and care. Additionally, there is a lack of awareness among residents in rural or mountainous areas about HIV/AIDS infection, as provided by healthcare professionals. Until now, research data have been scarce on the demographic characteristics, clinical features, and treatment approaches for HIV/AIDS patients in the interior regions of Papua. This data is crucial for devising strategies aimed at enhancing healthcare services for individuals affected by HIV/AIDS.Consequently, this study endeavors to gain insights into the demographic characteristics, clinical features, and treatment modalities for HIV/AIDS patients at the Regional General Hospital of the Central Papua Region. It employs an observational descriptive approach, utilizing medical records of HIV/AIDS patients who visited the Central Papua Regional Government Hospital in June 2023. The findings indicate that, based on demographic data, the majority of patients were, on average, ≤25 years old (60.8%), male (52.5%), married (56.7%), and the highest number of HIV/AIDS cases were among secondary education graduates (40.8%). The majority were employed (67.5%) with incomes below the minimum wage threshold (69.2%). All heterosexual patients exhibited behavioral risk factors, and 4.2% had comorbidities such as hypertension. Tuberculosis was the most common opportunistic infection (17.5%). The highest proportion of individuals with HIV/AIDS were in stage II (66.7%). The predominant antiretroviral treatment regimen was a fixed-dose combination (FDC) containing Tenofovir 300mg, Lamivudine 300mg, and Efavirenz 600mg. The duration of use of ARV therapy in people with HIV / AIDS is at most 1 month.